A COMPARATIVE STUDY OF LITERACY RATE OF NORTH TRIPURA, UNAKOTI AND BARAK VALLEY OF ASSAM - Singha, Manindra (International Journal For Research In Business, Management And Accounting, 2020)
The literacy rate of any community is the barometer of the situation of education in any society. Manipuris both in the study areas found a viable percentage of literacy rate even though in a remote arrear of both the state. Right from the number of person who can write his or her name correctly and upto the higher level of degrees given by the Universities of different state and central Universities. So, literacy rate high means the entrance in the educational institution in multidimensional way.